Strategic Management and Organizational Policies Against Corruption - Rüzgar, Nilüfer (IGI Global, 2023)
Strategic management is the identification and description of the strategies that managers implement in order to achieve their organizational long-term goals via better performance and gaining competitive advantage in the process. Corruption, on the other hand, is known as dishonest or fraudulent conduct by the people/managers in power. In this sense, it becomes inevitable in organizations, where there is always a conflict of interests, not to experience corruption behavior. At this point, preventing and coping with corruption constitutes importance. In this context, the purpose of this chapter is to scrutinize the literature in the frame of strategic management, strategy, organizational policies, corruption, and the strategies and policies that are effective for coping with corruption. In addition, the chapter also consists of some international corruption scandal examples. © 2023 by IGI Global.